Factors of influence on the formation of empathic culture among students of higher education - Yuantsi, Li; Popova, Olena (Professional Art Education, 2024)
The article is devoted to the problem of forming an empathetic culture of the future teacher, the relevance of which at the socio-pedagogical level is determined by the need of modern society for teachers who are capable of compassion, empathy, who possess tolerance and empathy as a professional value; on the theoretical and methodological level - the need to create theoretical foundations for the formation of empathic culture of future teachers during professional training; on the methodological and technological level - the need to develop a system of educational and methodological support for the formation of a defined culture of future teachers. Object (the purpose and task of the research). The purpose of the study is to analyze the views of Chinese scientists regarding factors influencing the formation of empathetic culture of higher education students in order to enrich the theoretical foundations of solving the problem. Achieving the set goal requires clarifying the key concepts of the research "empathic culture", "formation of empathic culture". Research results. The article focuses on the fact that, being a complex and multifaceted phenomenon, empathic culture among students does not arise spontaneously, but requires purposeful formation of this personality quality of the future teacher. The concept of "formation of empathic culture" of students is considered as a process aimed at their acquisition of special knowledge and mastery of empathic skills. The views of Chinese scientists regarding factors influencing the formation of the empathic culture of future specialists, in particular music teachers, were analyzed: macro factors (socio-cultural and economic factors; family environment and family education); cultivation of moral virtues and practical application of socialist core values; participation in communication with representatives of various social groups; personal factors (cognitive and emotional abilities, the ability to sympathize and empathize), etc. Conclusions. In today’s society, it can be found that the ability and level of empathy of college students are generally not high, which indicates that there are many opportunities for improvement, and the results of Chinese scientists and researchers have shown that the formation of an empathic culture of students, including future teachers -musicians, attention should be increased. The factors of formation of empathic culture of students, which are researched by Chinese scientists, were analyzed (macro factors, pedagogical and personal factors). It is noted that taking into account these factors makes it possible to choose the right strategies for the formation of empathic culture of future teachers.